Humane considerations and two examples of traditional slaughtering - Bartosiewicz, László; Csiky, Gergely; Gyarmati, János (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
In modern western terms, an animal carcass is considered as a hazardous waste. Animals that died of disease or old age cannot be consumed, although we take natural that most of us would eat the meat of creatures that were killed. However, an important aspect – both technical and mental – is represented by the fact that „properly” slaughtered animals are killed with a single cut across the throat and thoroughly bled. This latter point remains fundamental, even if animals are killed by using modern, industrial equipment such as the compressed air-gun or electricity. In purely practical, hygienic terms, draining the blood of freshly killed animals means that bacteria, especially those concentrated in the digestive tract, cannot infest the rest of the dead body through the bloodstream. This rational ideology, however, seems deeply rooted in the traditional Judeo-Christian-Moslem way of slaughtering animals that may have been a difficult (although not impossible) task prior to the wide availability of metal blades.It must have been these archaic times, when a technique developed, by which the animals blood circulation is disrupted by hand, reaching through an opening cut into the victim’s side. This method could be observed independently from each other in Bolivia and Mongolia.Remarkably, many of the more recent, ritual forms of slaughter (similarly to modern, western regulations) stress the importance of minimizing the animals’ suffering. Meanwhile, differing attitudes to the modes of slaughter have often reflected major ideological differences throughout culture history, as ethnic and religious tensions surfaced referring to the welfare of livestock to be killed. This paper reviews the problem quoting archaeozoological and ethnographic examples from Europe, the Near East, South America and Central Asia.
Keywords: slaughtering; carrion; archaeozoology; kosher; halāl